Postural Mechanisms That Maintain Airway Adequacy In Obstructive Sleep Apnoea As Determined By Magnetic Resonance Imaging - Avcı, Suat; Yılmaz Avcı, Aynur (ENT Updates, 2018)
Objective: This magnetic resonance imaging (MRI) study aimed to explored associations between neutral head posture, size, and shape of the pharyngeal airway and the severity of obstructive sleep apnoea (OSA). Methods: A retrospective methodology was used to study 90 male patients who had already undergone overnight polysomnography and cervical MRI. 60 cases of OSA were compared with a control group of 30 mild OSA (or straightforward snoring) cases in terms of MRI, with the aim to examine how neutral head posture, the pharynx and the adjacent anatomical structures interact. MRI was performed in all cases with the patient supine and head held in neutral position. Measurements were taken of the Craniocervical extension (CCE) and epiglot angle, length of the tongue root, distance between the hyoid and the plane of the mandible (MP-H distance), and the diameter of the pharyngeal airway at seven points were measured. Results: Differences in shape were more perceptible at the caudal levels. In the OSA group, the shapes were more oblique. The retroglossal level was where the largest shape difference was apparent. After adjusting for body mass index and age, neutral head posture was correlated with OSA severity. There was a correlation between CCE and lengthening of the tongue root, MP-H distance, epiglot angle, and the two most caudal airway areas. Conclusions: Overall, increased length of the root of the tongue, MP-H distance, and epiglot angle are associated with CCE in OSA patients and resulted in a larger and more oblique airway in the majority of caudal planes. Such an alteration may be viewed as an adaptation in posture designed to keep the airway sufficiently open in patients suffering from OSA.